Effect of Platelet-Activating Factor on Barrier Function of ARPE-19 Cells - Zhang F; Liu L; Zhang H; Liu ZL (Dove Medical Press, 2020)
Fan Zhang,1 Lei Liu,2 Han Zhang,2 Zhe-Li Liu2 1Department of Ophthalmology, The Fourth Affiliated Hospital of China Medical University, Eye Hospital of China Medical University, Key Lens Research Laboratory of Liaoning Province, Shenyang, Liaoning, People’s Republic of China; 2Department of Ophthalmology, The First Affiliated Hospital of China Medical University, Shenyang, Liaoning, People’s Republic of ChinaCorrespondence: Han ZhangDepartment of Ophthalmology, The First Affiliated Hospital of China Medical University, 155 Nanjing North St, Heping District, Shenyang 110001, Liaoning, People’s Republic of ChinaTel +86-24-83283590Fax +86-24-83282997Email zhanghan0614@139.comAim: To examine the effects of platelet-activating factor (PAF) on the barrier functions of cultured retinal pigment epithelial (RPE) cells.Methods: A human RPE cell line (ARPE-19) was cultured on microporous filter supports and treated with PAF and WEB 2086, a specific PAF-receptor (PAF-R) antagonist. The permeability of the RPE monolayer was measured using transepithelial electrical resistance (TER) and sodium fluorescein flux. The expression of the tight junction protein zonula occludens (ZO)-1 and the adherens junction protein N-cadherin was assessed using immunohistochemistry and Western blotting. We also measured the vascular endothelial growth factor (VEGF) concentrations in PAF-treated cultures and re-measured RPE monolayer permeability in the presence of VEGF-neutralizing antibodies.Results: PAF significantly decreased the TER and enhanced the sodium fluorescein flux of the RPE monolayer and downregulated the expression of ZO-1 and N-cadherin. These effects were abolished by WEB 2086-mediated blockage of the PAF-R. PAF stimulation increased VEGF expression in RPE cells, and the antibody-mediated neutralization of VEGF caused a partial recovery of the barrier properties.Conclusion: The barrier functions of ARPE-19 cells were altered by PAF, and these effects were partly mediated by an upregulation of VEGF expression in these cells. Our results contribute to the growing body of evidence supporting the role of PAF in choroidal neovascularization. Our findings suggest that PAF is a novel target in the development of therapies for increased permeability of the RPE monolayer.Keywords: platelet-activating factor, ARPE-19 cells, barrier function, vascular endothelial growth factor